2013
DOI: 10.3109/02770903.2013.831872
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for persistence of asthma in children: 10-year follow-up

Abstract: Atopy, presence of rhinitis, positive and presence of bronchial hyper-reactivity are important risk factors for the persistence of asthma in children. Allergen-induced CD4(+)CD25(+) T cells were higher in the atopic children who outgrew their disease, implicating an immunological mechanism of asthma remission in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…A very recent cross-sectional study confirmed that the mothers’ depression negatively affected the lives of their asthmatic children, and was correlated with an increased number of emergency department visits [18]. On the other hand, it has been reported that the psychological health of the parents is strongly affected by their child’s chronic disease [19,20]. Moreover, Wamboldt evaluated the parents, usually the mothers, of 62 adolescents admitted to a tertiary care asthma center for severe asthma, and showed a link between severe asthma and familial affective disorders [21].…”
Section: Discussionmentioning
confidence: 99%
“…A very recent cross-sectional study confirmed that the mothers’ depression negatively affected the lives of their asthmatic children, and was correlated with an increased number of emergency department visits [18]. On the other hand, it has been reported that the psychological health of the parents is strongly affected by their child’s chronic disease [19,20]. Moreover, Wamboldt evaluated the parents, usually the mothers, of 62 adolescents admitted to a tertiary care asthma center for severe asthma, and showed a link between severe asthma and familial affective disorders [21].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the studies found a higher proportion of clinical asthma remission (ranging 10-30%) than the complete asthma remission status (ranging 5-22%). Two studies however, found higher prevalence proportions of complete compared to clinical remission (Aydogan et al, 2013;Westerhof et al, 2018) . An explanation for this difference could be that Westerhof et al used a N4mg/ml methacholine threshold cut-off, classifying clinical remission subjects with mild bronchial hyperresponsiveness in the complete remission group.…”
Section: The Prevalence Of Clinical and Complete Asthma Remissionmentioning
confidence: 95%
“…or "No". We selected the minimum sufficient adjusted set of confounders using the modified disjunctive cause criterion, informed by evidence in the current literature and a directed acyclic graph (DAG) (Fig 2) (1,7,(13)(14)(15)(16)(17). As cat ownership is not an important risk factor for T. gondii infection, and pet ownership information was not collected in the 2012-2014 NHANES, cat ownership was not included as a covariate (18)(19)(20)(21)(22)(23).…”
Section: Methodsmentioning
confidence: 99%
“…Number of children in the household was 0-3 or greater than 4 (9). It is not clear from the literature if level of education is associated with asthma after adjusting for income (13,24). We calculated Akaike information criteria (AICs) for the ordinal and logistic regression models with and without the variable "education of the household reference person" to evaluate model fit.…”
Section: Methodsmentioning
confidence: 99%